(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article deals with the experience of translating historical novels in translation studies. It provides a comparative analysis of the specific methods of the Uzbek national school of translation studies and the world schools of translation. Moreover, the genesis of translation of Uzbek historical novels, methods of translation, especially the problem of technique in the translation into English, and certain peculiarities of translating historical works are studied here on a scientific basis. As a result, a number of scientific and practical recommendations are given to improve the mechanisms of forming professional competence in the practice of translating historical novels, with the experimental trends of world translation schools taken into account.